Chemotherapy Plus Cetuximab versus Chemotherapy Alone for Patients with KRAS Wild Type Unresectable Liver-Confined Metastases Colorectal Cancer: An Updated Meta-Analysis of RCTs. (11th January 2017) - Lv, W.; Zhang, G. Q.; Jiao, A.; Zhao, B. C.; Shi, Y.; Chen, B. M.; Zhang, J. L.
Abstract : Purpose. Our study analyses clinical trials and evaluates the efficacy of adding cetuximab in systematic chemotherapy for unresectable colorectal cancer liver-confined metastases patients. Materials and Methods. Search EMBASE, PubMed, and the Cochrane Central Register of Controlled Trials for RCTs comparing chemotherapy plus cetuximab with chemotherapy alone for KRAS wild type patients with colorectal cancer liver metastases (CRLMs). We calculated the relative risks (RRs) with 95% confidence interval and performed meta-analysis of hazard ratios (HRs) for the R0 resection rate, the overall response rate (ORR), the progression-free survival (PFS) and overall survival (OS). Results. 1173 articles were retrieved and 4 RCTs were available for our study. The four studies involved 504 KRAS wild type patients with CRLMs. The addition of cetuximab significantly improved all the 4 outcomes: the R0 resection rate (RR 2.03, p = 0.004 ), the ORR (RR 1.76, p < 0.00001 ), PFS (HR 0.63, p < 0.0001 ), and also OS (HR 0.74, p = 0.04 ); the last outcome is quite different from the conclusion published before. Conclusions. Although the number of patients analysed was limited, we found that the addition of cetuximab significantly improves the outcomes in KRAS wild type patients with unresectable colorectal cancer liver-confined metastases. Cetuximab combined with systematic chemotherapy perhaps suggests a promising choice for KRAS wild type patients with unresectable liver metastases.